Environment-friendly high-toughness fiber reinforced composite material and preparation method thereof
By using environmentally friendly high-tough fiber reinforced composite materials in wall materials, the problem of easy separation of existing wall materials in water corrosion environments is solved, higher adhesion and waterproof performance are achieved, and the overall load-bearing capacity of the wall is enhanced.
Patent Information
- Application Number
- CN202411656307.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-25
AI Technical Summary
Existing wall materials can easily lead to the separation of cement and bricks in long-term water corrosion environments, reducing the support and waterproofing of the walls, and increasing the risk of collapse or leakage.
The environmentally friendly high-tough fiber reinforced composite material is used to prepare composite materials with higher permeability and adhesion through the combination of carbon fiber, modified reinforcement resin, thermally scattered fiber microsheets and cement base materials, combined with laser treatment and vibration mixing and other processes.
It improves the adhesion and traction of wall materials, enhances the support capacity and waterproof performance of the wall, reduces the risk of separation between materials and bricks, and extends the service life of the wall.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wall materials, and in particular relates to an environmentally friendly high-tenacity fiber-reinforced composite material and a preparation method thereof. Background Art
[0002] Wall materials are raw materials used to build walls in buildings. They not only bear the weight of the building, but also play a role in maintenance and partition. The choice of wall materials has an important impact on the building's load-bearing capacity, thermal insulation performance, sound insulation performance and aesthetics.
[0003] At present, most walls are built with bricks and cement. When used in an environment with long-term water corrosion, such as a bathroom, the cement in the wall is easily separated from the bricks under long-term water corrosion, resulting in weakened wall support and increased risks of wall collapse or ground collapse, as well as damaged waterproof performance, causing seepage and leakage problems. Summary of the invention
[0004] The purpose of the present invention is to provide an environmentally friendly high-tenacity fiber-reinforced composite material and a preparation method thereof in order to solve the above-mentioned problems.
[0005] The present invention achieves the above-mentioned purpose through the following technical solutions:
[0006] The present invention provides an environmentally friendly high-tenacity fiber-reinforced composite material and a preparation method thereof. The raw materials for the preparation include, by weight:
[0007] 20-25 parts of carbon fiber, 30-45 parts of modified reinforcing resin, 10-18 parts of heat-transmitting fiber microsheets, 35-45 parts of cement base material, 10-15 parts of surfactant, 10-13 parts of surface toughening agent, 10-20 parts of styrene-butadiene-styrene block copolymer;
[0008] Wherein, the raw materials for preparing the heat-transmitting fiber micro-sheets include, by weight: 3-6 parts of copper powder, 15-25 parts of kenaf fiber powder, 5-8 parts of adhesive, and 15-25 parts of silk sheets.
[0009] As a further optimization scheme of the present invention, the preparation process of the carbon fiber is:
[0010] (i) subjecting the surfaces of carbon fiber precursors with diameters of 0.01-0.03 μm, 0.1-0.3 μm, and 1-3 μm to laser treatment, and etching 10-30 grooves with a radius of 0.001-0.003 μm on the surfaces of the carbon fiber precursors; (ii) vibrating and mixing the carbon fiber precursors with diameters of 0.01-0.03 μm, 0.1-0.3 μm, and 1-3 μm using a vibration disk, and controlling the vibration time to be 15 min-25 min.
[0011] As a further optimization scheme of the present invention, the raw materials for preparing the carbon fiber include, by weight:
[0012] 5-8 parts of 0.01-0.03 μm carbon fiber precursor, 10-15 parts of 0.1-0.3 μm carbon fiber precursor and 10-15 parts of 1-3 μm carbon fiber precursor.
[0013] As a further optimization scheme of the present invention, the preparation process of the modified reinforced resin is:
[0014] (i) Mixing and stirring liquid nitrile rubber and polyvinyl alcohol tert-butyral for 10-20 min, at a stirring speed of 100-120 r / min and at a temperature of 25-30°C to obtain a mixed rubber; (ii) Mixing and stirring vinyl acetate, Yajing stone and Jingzuancai for 15-25 min, at a stirring speed of 100-120 r / min and at a temperature of 25-30°C to obtain a mixture; (iii) Mixing and stirring the mixed rubber, the mixture and epoxy resin for 40-60 min, at a stirring speed of 60-80 r / min and at a temperature of 25-30°C.
[0015] As a further optimization scheme of the present invention, the raw materials for preparing the modified reinforced resin include, by weight:
[0016] 10-15 parts of liquid nitrile rubber, 10-15 parts of polyvinyl alcohol tert-butyral, 3-6 parts of vinyl acetate, 3-6 parts of Yajing stone, 3-6 parts of Jingzuancai and 30-45 parts of epoxy resin.
[0017] As a further optimization scheme of the present invention, the preparation process of the heat-transmitting fiber microsheet is as follows:
[0018] (i) mixing copper powder with a diameter of 4-7 μm and kenaf fiber powder with a diameter of 0.5-0.8 nm for 15-25 min and a stirring speed of 30-50 r / min to obtain a mixture; (ii) using a textile machine to weave silk into 10-15 cm silk sheets, and spraying an adhesive on the silk sheets; (iii) using a vibrating spreader to evenly scatter the mixture on the silk sheets, and air-drying the silk sheets naturally; (iv) cutting the silk sheets to obtain 3-6 nm heat-transmitting fiber microsheets.
[0019] As a further optimization scheme of the present invention, the preparation process of the kenaf fiber is as follows:
[0020] (i) Take kenaf leaves, wash them and dry them; (ii) Roll them under a stone mill; (iii) Spread the rolled kenaf leaves flat on a screen; (iv) Use a high-pressure water gun to wash the juice out of the rolling, and keep the fiber strands for later use; (v) Use a vulcanizing agent at 110-120° C. to spray the fiber strands for 4-6 hours, and then use 60-70° C. hot air to blow the fiber strands until the fiber strands are completely dry; (v) Grind the fiber strands to obtain kenaf fiber powder.
[0021] A method for preparing the above-mentioned environmentally friendly high-tenacity fiber-reinforced composite material is characterized by comprising the following steps:
[0022] S1, mixing rubber grass rubber and α-cyanoacrylate glue solution (the mass ratio of rubber grass rubber to α-cyanoacrylate glue solution is 1:1) to obtain a surface toughening agent;
[0023] S2, mixing a cement base material and a styrene-butadiene-styrene block copolymer to obtain a base material mixture;
[0024] S3, mixing the base material mixture and the surfactant to obtain a permeable base material;
[0025] S4, mixing carbon fibers, modified reinforcing resin, heat-permeable fiber microsheets, surface toughening agents and permeable base materials to obtain an environmentally friendly high-toughness fiber-reinforced composite material.
[0026] The beneficial effects of the present invention are as follows: through the use of heat-permeable fiber microsheets, the composite material has better penetration ability, and more composite material penetrates into the interior of the brick through the pores on the brick, so that the composite material has better adhesion ability, thereby improving the traction between the bricks, and at the same time, it also helps to avoid the separation of the composite material and the bricks, thereby ensuring the support capacity and waterproof ability of the wall as much as possible; through the coordinated use of carbon fiber precursors of different sizes, the force-bearing capacity of the brick masonry is effectively improved, and the subsequent application to the building wall can effectively enhance the force-bearing capacity and anti-destruction ability of the wall; through the use of surface toughening agents, the surface of the composite material solidifies the fastest, which helps to shorten the construction period, and at the same time, reduces the probability of debris and dust at the construction site adhering to the surface of the composite material. DETAILED DESCRIPTION
[0027] The present application is described in further detail below. It is necessary to point out that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technicians in this field can make some non-essential improvements and adjustments to the present application based on the above application content.
[0028] 1. Materials
[0029] Unless otherwise specified, the methods used in the present invention are conventional methods known to those skilled in the art, and the reagents and other materials used are commercially available products unless otherwise specified.
[0030] (1) In the present invention;
[0031] The vulcanizing agent in the present invention is XG-818 platinum vulcanizing agent under the Haocheng brand.
[0032] 2. Embodiment
[0033] Example 1
[0034] The environmentally friendly high-tenacity fiber-reinforced composite material, calculated by weight, comprises the following raw materials:
[0035] 20 parts of carbon fiber, 30 parts of modified reinforcing resin, 10 parts of heat-transmitting fiber microsheets, 35 parts of cement base material, 10 parts of surfactant, 10 parts of surface toughening agent, 10 parts of styrene-butadiene-styrene block copolymer;
[0036] The raw materials for preparing the heat-transmitting fiber micro-sheets include, by weight: 3 parts of copper powder, 15 parts of kenaf fiber powder, 5 parts of adhesive, and 15 parts of silk sheets;
[0037] The raw materials for preparing carbon fiber include, by weight: 5 parts of 0.01 μm carbon fiber precursor, 10 parts of 0.1 μm carbon fiber precursor and 10 parts of 1 μm carbon fiber precursor;
[0038] The raw materials for preparing the modified reinforced resin include, by weight: 10 parts of liquid nitrile rubber, 10 parts of polyvinyl alcohol tert-butyral, 3 parts of vinyl acetate, 3 parts of Yajing stone, 3 parts of Jingzuancai and 30 parts of epoxy resin;
[0039] A method for preparing the above-mentioned environmentally friendly high-tenacity fiber-reinforced composite material comprises the following steps:
[0040] Carbon fiber: (i) The surface of carbon fiber precursors with diameters of 0.01 μm, 0.1 μm, and 1 μm was laser treated, and 10 grooves with a radius of 0.001 μm were etched on the surface of the carbon fiber precursors; (ii) The carbon fiber precursors with diameters of 0.01 μm, 0.1 μm, and 1 μm were vibrated and mixed using a vibration plate, and the vibration time was controlled to be 15 min;
[0041] Modified reinforced resin: (i) Liquid nitrile rubber and polyvinyl alcohol tert-butyral are mixed and stirred for 10 minutes, at a stirring speed of 100 r / min and at a temperature of 25°C to obtain a mixed glue; (ii) Vinyl acetate, Yajing stone and Jingzuancai are mixed and stirred for 15 minutes, at a stirring speed of 100 r / min and at a temperature of 25°C to obtain a mixture; (iii) The mixed glue, the mixture and epoxy resin are mixed and stirred for 40 minutes, at a stirring speed of 60 r / min and at a temperature of 25°C;
[0042] Kenaf fiber: (i) taking kenaf leaves, washing them, and drying them; (ii) rolling them under a stone mill; (iii) spreading the rolled kenaf leaves flat on a screen; (iv) using a high-pressure water gun to wash the juice out of the rolling, leaving the fiber strands for later use; (v) spraying the fiber strands with a vulcanizing agent at 110°C for 4 hours, and then drying the fiber strands with hot air at 60°C until the fiber strands are completely dry; (v) grinding the fiber strands to obtain kenaf fiber powder;
[0043] Heat-transmitting fiber micro-sheets: (i) copper powder with a diameter of 4 μm and kenaf fiber powder with a diameter of 0.5 nm are mixed and stirred for 15 min at a stirring speed of 30 r / min to obtain a mixture; (ii) silk is woven into a 10 cm silk sheet using a textile machine, and an adhesive is sprayed on the silk sheet; (iii) the mixture is evenly spread on the silk sheet using a vibrating spreader, and the mixture is naturally air-dried; (iv) the silk sheet is cut to obtain a 3 nm heat-transmitting fiber micro-sheet;
[0044] The rubber grass rubber and the α-cyanoacrylate glue solution are mixed (the mass ratio of the rubber grass rubber to the α-cyanoacrylate glue solution is 1:1) to obtain a surface toughening agent;
[0045] Mixing a cement base material and a styrene-butadiene-styrene block copolymer to obtain a base material mixture;
[0046] mixing the base material mixture and the surfactant to obtain a permeable base material;
[0047] Carbon fibers, modified reinforcing resin, heat-permeable fiber microsheets and permeable base materials are mixed to obtain an environmentally friendly high-tenacity fiber-reinforced composite material.
[0048] Example 2
[0049] The environmentally friendly high-tenacity fiber-reinforced composite material, calculated by weight, comprises the following raw materials:
[0050] 23 parts of carbon fiber, 38 parts of modified reinforcing resin, 14 parts of heat-transmitting fiber microsheets, 40 parts of cement base material, 13 parts of surfactant, 12 parts of surface toughening agent, 15 parts of styrene-butadiene-styrene block copolymer;
[0051] The raw materials for preparing the heat-transmitting fiber micro-sheets include, by weight: 5 parts of copper powder, 20 parts of kenaf fiber powder, 7 parts of adhesive, and 20 parts of silk sheets;
[0052] The raw materials for preparing carbon fiber include, by weight: 7 parts of 0.02 μm carbon fiber precursor, 13 parts of 0.2 μm carbon fiber precursor and 13 parts of 2 μm carbon fiber precursor;
[0053] The raw materials for preparing the modified reinforced resin include, by weight: 13 parts of liquid nitrile rubber, 13 parts of polyvinyl alcohol tert-butyral, 5 parts of vinyl acetate, 5 parts of Yajing stone, 5 parts of Jingzuancai and 38 parts of epoxy resin;
[0054] A method for preparing the above-mentioned environmentally friendly high-tenacity fiber-reinforced composite material comprises the following steps:
[0055] Carbon fiber: (i) The surface of carbon fiber precursors with diameters of 0.02 μm, 0.2 μm, and 2 μm was laser treated, and 20 grooves with a radius of 0.002 μm were etched on the surface of the carbon fiber precursors; (ii) The carbon fiber precursors with diameters of 0.02 μm, 0.2 μm, and 2 μm were vibrated and mixed using a vibration plate, and the vibration time was controlled to be 20 min;
[0056] Modified reinforced resin: (i) Liquid nitrile rubber and polyvinyl alcohol tert-butyral are mixed and stirred for 15 minutes, at a stirring speed of 110 r / min and at a temperature of 28°C to obtain a mixed glue; (ii) Vinyl acetate, Yajing stone and Jingzuancai are mixed and stirred for 20 minutes, at a stirring speed of 110 r / min and at a temperature of 28°C to obtain a mixture; (iii) The mixed glue, the mixture and epoxy resin are mixed and stirred for 50 minutes, at a stirring speed of 70 r / min and at a temperature of 28°C;
[0057] Kenaf fiber: (i) taking kenaf leaves, washing them, and drying them; (ii) rolling them under a stone mill; (iii) spreading the rolled kenaf leaves flat on a screen; (iv) using a high-pressure water gun to wash the juice out of the rolling, leaving the fiber strands for later use; (v) spraying the fiber strands with a vulcanizing agent at 115°C for 5 hours, and then drying the fiber strands with hot air at 65°C until the fiber strands are completely dry; (v) grinding the fiber strands to obtain kenaf fiber powder;
[0058] Heat-transmitting fiber micro-sheets: (i) copper powder with a diameter of 6 μm and kenaf fiber powder with a diameter of 0.7 nm are mixed and stirred for 20 min at a stirring speed of 40 r / min to obtain a mixture; (ii) silk is woven into a 13 cm silk sheet using a textile machine, and an adhesive is sprayed on the silk sheet; (iii) the mixture is evenly spread on the silk sheet using a vibrating spreader, and the mixture is naturally air-dried; (iv) the silk sheet is cut to obtain a 5 nm heat-transmitting fiber micro-sheet;
[0059] The rubber grass rubber and the α-cyanoacrylate glue solution are mixed (the mass ratio of the rubber grass rubber to the α-cyanoacrylate glue solution is 1:1) to obtain a surface toughening agent;
[0060] Mixing a cement base material and a styrene-butadiene-styrene block copolymer to obtain a base material mixture;
[0061] mixing the base material mixture and the surfactant to obtain a permeable base material;
[0062] Carbon fibers, modified reinforcing resin, heat-permeable fiber microsheets and permeable base materials are mixed to obtain an environmentally friendly high-tenacity fiber-reinforced composite material.
[0063] Example 3
[0064] The environmentally friendly high-tenacity fiber-reinforced composite material, calculated by weight, comprises the following raw materials:
[0065] 25 parts of carbon fiber, 45 parts of modified reinforcing resin, 18 parts of heat-transmitting fiber microsheets, 45 parts of cement base material, 15 parts of surfactant, 13 parts of surface toughening agent, 20 parts of styrene-butadiene-styrene block copolymer;
[0066] The raw materials for preparing the heat-transmitting fiber micro-sheets include, by weight: 6 parts of copper powder, 25 parts of kenaf fiber powder, 8 parts of adhesive, and 25 parts of silk sheets;
[0067] The raw materials for preparing carbon fiber include, by weight: 8 parts of 0.03 μm carbon fiber precursor, 15 parts of 0.3 μm carbon fiber precursor and 15 parts of 3 μm carbon fiber precursor;
[0068] The raw materials for preparing the modified reinforced resin include, by weight: 15 parts of liquid nitrile rubber, 15 parts of polyvinyl alcohol tert-butyral, 6 parts of vinyl acetate, 6 parts of Yajing stone, 6 parts of Jingzuancai and 45 parts of epoxy resin;
[0069] A method for preparing the above-mentioned environmentally friendly high-tenacity fiber-reinforced composite material comprises the following steps:
[0070] Carbon fiber: (i) The surface of carbon fiber precursors with diameters of 0.03 μm, 0.3 μm, and 3 μm was laser treated, and 30 grooves with a radius of 0.003 μm were etched on the surface of the carbon fiber precursors; (ii) The carbon fiber precursors with diameters of 0.03 μm, 0.3 μm, and 3 μm were vibrated and mixed using a vibration plate, and the vibration time was controlled to be 25 min;
[0071] Modified reinforced resin: (i) Liquid nitrile rubber and polyvinyl alcohol tert-butyral are mixed and stirred for 20 minutes, at a stirring speed of 120 r / min and at a temperature of 30°C to obtain a mixed glue; (ii) Vinyl acetate, Yajing stone and Jingzuancai are mixed and stirred for 25 minutes, at a stirring speed of 120 r / min and at a temperature of 30°C to obtain a mixture; (iii) The mixed glue, the mixture and epoxy resin are mixed and stirred for 60 minutes, at a stirring speed of 80 r / min and at a temperature of 30°C;
[0072] Kenaf fiber: (i) taking kenaf leaves, washing them, and drying them; (ii) rolling them under a stone mill; (iii) spreading the rolled kenaf leaves flat on a screen; (iv) using a high-pressure water gun to wash the juice out of the rolling, leaving the fiber strands for later use; (v) spraying the fiber strands with a vulcanizing agent at 120°C for 6 hours, and then drying the fiber strands with hot air at 70°C until the fiber strands are completely dry; (v) grinding the fiber strands to obtain kenaf fiber powder;
[0073] Heat-transmitting fiber micro-sheets: (i) copper powder with a diameter of 7 μm and kenaf fiber powder with a diameter of 0.8 nm are mixed and stirred for 25 min at a stirring speed of 50 r / min to obtain a mixture; (ii) silk is woven into a 15 cm silk sheet using a textile machine, and an adhesive is sprayed on the silk sheet; (iii) the mixture is evenly spread on the silk sheet using a vibrating spreader, and the mixture is naturally air-dried; (iv) the silk sheet is cut to obtain a 6 nm heat-transmitting fiber micro-sheet;
[0074] The rubber grass rubber and the α-cyanoacrylate glue solution are mixed (the mass ratio of the rubber grass rubber to the α-cyanoacrylate glue solution is 1:1) to obtain a surface toughening agent;
[0075] Mixing a cement base material and a styrene-butadiene-styrene block copolymer to obtain a base material mixture;
[0076] mixing the base material mixture and the surfactant to obtain a permeable base material;
[0077] Carbon fibers, modified reinforcing resin, heat-permeable fiber microsheets and permeable base materials are mixed to obtain an environmentally friendly high-tenacity fiber-reinforced composite material.
[0078] Comparative Example 1
[0079] The environmentally friendly high-tenacity fiber-reinforced composite material, calculated by weight, comprises the following raw materials:
[0080] 25 parts of carbon fiber, 45 parts of modified reinforcing resin, 18 parts of heat-transmitting fiber microsheets, 45 parts of cement base material, 15 parts of surfactant, 13 parts of surface toughening agent, 20 parts of styrene-butadiene-styrene block copolymer;
[0081] The raw materials for preparing the heat-transmitting fiber micro-sheets include, by weight: 6 parts of copper powder, 25 parts of kenaf fiber powder, 8 parts of adhesive, and 25 parts of silk sheets;
[0082] The raw materials for preparing carbon fiber include, by weight: 19 parts of 0.3 μm carbon fiber precursor and 19 parts of 3 μm carbon fiber precursor;
[0083] The raw materials for preparing the modified reinforced resin include, by weight: 15 parts of liquid nitrile rubber, 15 parts of polyvinyl alcohol tert-butyral, 6 parts of vinyl acetate, 6 parts of Yajing stone, 6 parts of Jingzuancai and 45 parts of epoxy resin;
[0084] A method for preparing the above-mentioned environmentally friendly high-tenacity fiber-reinforced composite material comprises the following steps:
[0085] Carbon fiber: (i) The surface of carbon fiber precursors with diameters of 0.3 μm and 3 μm was laser treated, and 30 grooves with a radius of 0.003 μm were etched on the surface of the carbon fiber precursors; (ii) The carbon fiber precursors with diameters of 0.3 μm and 3 μm were vibrated and mixed using a vibration plate, and the vibration time was controlled to be 25 min;
[0086] Modified reinforced resin: (i) Liquid nitrile rubber and polyvinyl alcohol tert-butyral are mixed and stirred for 20 minutes, at a stirring speed of 120 r / min and at a temperature of 30°C to obtain a mixed glue; (ii) Vinyl acetate, Yajing stone and Jingzuancai are mixed and stirred for 25 minutes, at a stirring speed of 120 r / min and at a temperature of 30°C to obtain a mixture; (iii) The mixed glue, the mixture and epoxy resin are mixed and stirred for 60 minutes, at a stirring speed of 80 r / min and at a temperature of 30°C;
[0087] Kenaf fiber: (i) taking kenaf leaves, washing them, and drying them; (ii) rolling them under a stone mill; (iii) spreading the rolled kenaf leaves flat on a screen; (iv) using a high-pressure water gun to wash the juice out of the rolling, leaving the fiber strands for later use; (v) spraying the fiber strands with a vulcanizing agent at 120°C for 6 hours, and then drying the fiber strands with hot air at 70°C until the fiber strands are completely dry; (v) grinding the fiber strands to obtain kenaf fiber powder;
[0088] Heat-transmitting fiber micro-sheets: (i) copper powder with a diameter of 7 μm and kenaf fiber powder with a diameter of 0.8 nm are mixed and stirred for 25 min at a stirring speed of 50 r / min to obtain a mixture; (ii) silk is woven into a 15 cm silk sheet using a textile machine, and an adhesive is sprayed on the silk sheet; (iii) the mixture is evenly spread on the silk sheet using a vibrating spreader, and the mixture is naturally air-dried; (iv) the silk sheet is cut to obtain a 6 nm heat-transmitting fiber micro-sheet;
[0089] The rubber grass rubber and the α-cyanoacrylate glue solution are mixed (the mass ratio of the rubber grass rubber to the α-cyanoacrylate glue solution is 1:1) to obtain a surface toughening agent;
[0090] Mixing a cement base material and a styrene-butadiene-styrene block copolymer to obtain a base material mixture;
[0091] mixing the base material mixture and the surfactant to obtain a permeable base material;
[0092] Carbon fibers, modified reinforcing resin, heat-permeable fiber microsheets and permeable base materials are mixed to obtain an environmentally friendly high-tenacity fiber-reinforced composite material.
[0093] Comparative Example 2
[0094] The environmentally friendly high-tenacity fiber-reinforced composite material, calculated by weight, comprises the following raw materials:
[0095] 25 parts of carbon fiber, 45 parts of modified reinforcing resin, 18 parts of heat-transmitting fiber microsheets, 45 parts of cement base material, 15 parts of surfactant, 13 parts of surface toughening agent, 20 parts of styrene-butadiene-styrene block copolymer;
[0096] The raw materials for preparing the heat-transmitting fiber micro-sheets include, by weight: 6 parts of copper powder, 25 parts of kenaf fiber powder, 8 parts of adhesive, and 25 parts of silk sheets;
[0097] The raw materials for preparing carbon fiber include, by weight: 13 parts of 0.03 μm carbon fiber precursor and 25 parts of 3 μm carbon fiber precursor;
[0098] The raw materials for preparing the modified reinforced resin include, by weight: 15 parts of liquid nitrile rubber, 15 parts of polyvinyl alcohol tert-butyral, 6 parts of vinyl acetate, 6 parts of Yajing stone, 6 parts of Jingzuancai and 45 parts of epoxy resin;
[0099] A method for preparing the above-mentioned environmentally friendly high-tenacity fiber-reinforced composite material comprises the following steps:
[0100] Carbon fiber: (i) The surface of carbon fiber precursors with diameters of 0.03 μm and 3 μm was laser treated, and 30 grooves with a radius of 0.003 μm were etched on the surface of the carbon fiber precursors; (ii) The carbon fiber precursors with diameters of 0.03 μm and 3 μm were vibrated and mixed using a vibration plate, and the vibration time was controlled to be 25 min;
[0101] Modified reinforced resin: (i) Liquid nitrile rubber and polyvinyl alcohol tert-butyral are mixed and stirred for 20 minutes, at a stirring speed of 120 r / min and at a temperature of 30°C to obtain a mixed glue; (ii) Vinyl acetate, Yajing stone and Jingzuancai are mixed and stirred for 25 minutes, at a stirring speed of 120 r / min and at a temperature of 30°C to obtain a mixture; (iii) The mixed glue, the mixture and epoxy resin are mixed and stirred for 60 minutes, at a stirring speed of 80 r / min and at a temperature of 30°C;
[0102] Kenaf fiber: (i) taking kenaf leaves, washing them, and drying them; (ii) rolling them under a stone mill; (iii) spreading the rolled kenaf leaves flat on a screen; (iv) using a high-pressure water gun to wash the juice out of the rolling, leaving the fiber strands for later use; (v) spraying the fiber strands with a vulcanizing agent at 120°C for 6 hours, and then drying the fiber strands with hot air at 70°C until the fiber strands are completely dry; (v) grinding the fiber strands to obtain kenaf fiber powder;
[0103] Heat-transmitting fiber micro-sheets: (i) copper powder with a diameter of 7 μm and kenaf fiber powder with a diameter of 0.8 nm are mixed and stirred for 25 min at a stirring speed of 50 r / min to obtain a mixture; (ii) silk is woven into a 15 cm silk sheet using a textile machine, and an adhesive is sprayed on the silk sheet; (iii) the mixture is evenly spread on the silk sheet using a vibrating spreader, and the mixture is naturally air-dried; (iv) the silk sheet is cut to obtain a 6 nm heat-transmitting fiber micro-sheet;
[0104] The rubber grass rubber and the α-cyanoacrylate glue solution are mixed (the mass ratio of the rubber grass rubber to the α-cyanoacrylate glue solution is 1:1) to obtain a surface toughening agent;
[0105] Mixing a cement base material and a styrene-butadiene-styrene block copolymer to obtain a base material mixture;
[0106] mixing the base material mixture and the surfactant to obtain a permeable base material;
[0107] Carbon fibers, modified reinforcing resin, heat-permeable fiber microsheets and permeable base materials are mixed to obtain an environmentally friendly high-tenacity fiber-reinforced composite material.
[0108] Comparative Example 3
[0109] The environmentally friendly high-tenacity fiber-reinforced composite material, calculated by weight, comprises the following raw materials:
[0110] 25 parts of carbon fiber, 45 parts of modified reinforcing resin, 18 parts of heat-transmitting fiber microsheets, 45 parts of cement base material, 15 parts of surfactant, 13 parts of surface toughening agent, 20 parts of styrene-butadiene-styrene block copolymer;
[0111] The raw materials for preparing the heat-transmitting fiber micro-sheets include, by weight: 6 parts of copper powder, 25 parts of kenaf fiber powder, 8 parts of adhesive, and 25 parts of silk sheets;
[0112] The raw materials for preparing carbon fiber include, by weight: 13 parts of 0.03 μm carbon fiber precursor, 25 parts of 0.3 μm carbon fiber precursor;
[0113] The raw materials for preparing the modified reinforced resin include, by weight: 15 parts of liquid nitrile rubber, 15 parts of polyvinyl alcohol tert-butyral, 6 parts of vinyl acetate, 6 parts of Yajing stone, 6 parts of Jingzuancai and 45 parts of epoxy resin;
[0114] A method for preparing the above-mentioned environmentally friendly high-tenacity fiber-reinforced composite material comprises the following steps:
[0115] Carbon fiber: (i) The surface of carbon fiber precursors with diameters of 0.03 μm and 0.3 μm was laser treated, and 30 grooves with a radius of 0.003 μm were etched on the surface of the carbon fiber precursors; (ii) The carbon fiber precursors with diameters of 0.03 μm and 0.3 μm were vibrated and mixed using a vibration plate, and the vibration time was controlled to be 25 min;
[0116] Modified reinforced resin: (i) Liquid nitrile rubber and polyvinyl alcohol tert-butyral are mixed and stirred for 20 minutes, at a stirring speed of 120 r / min and at a temperature of 30°C to obtain a mixed glue; (ii) Vinyl acetate, Yajing stone and Jingzuancai are mixed and stirred for 25 minutes, at a stirring speed of 120 r / min and at a temperature of 30°C to obtain a mixture; (iii) The mixed glue, the mixture and epoxy resin are mixed and stirred for 60 minutes, at a stirring speed of 80 r / min and at a temperature of 30°C;
[0117] Kenaf fiber: (i) taking kenaf leaves, washing them, and drying them; (ii) rolling them under a stone mill; (iii) spreading the rolled kenaf leaves flat on a screen; (iv) using a high-pressure water gun to wash the juice out of the rolling, leaving the fiber strands for later use; (v) spraying the fiber strands with a vulcanizing agent at 120°C for 6 hours, and then drying the fiber strands with hot air at 70°C until the fiber strands are completely dry; (v) grinding the fiber strands to obtain kenaf fiber powder;
[0118] Heat-transmitting fiber micro-sheets: (i) copper powder with a diameter of 7 μm and kenaf fiber powder with a diameter of 0.8 nm are mixed and stirred for 25 min at a stirring speed of 50 r / min to obtain a mixture; (ii) silk is woven into a 15 cm silk sheet using a textile machine, and an adhesive is sprayed on the silk sheet; (iii) the mixture is evenly spread on the silk sheet using a vibrating spreader, and the mixture is naturally air-dried; (iv) the silk sheet is cut to obtain a 6 nm heat-transmitting fiber micro-sheet;
[0119] The rubber grass rubber and the α-cyanoacrylate glue solution are mixed (the mass ratio of the rubber grass rubber to the α-cyanoacrylate glue solution is 1:1) to obtain a surface toughening agent;
[0120] Mixing a cement base material and a styrene-butadiene-styrene block copolymer to obtain a base material mixture;
[0121] mixing the base material mixture and the surfactant to obtain a permeable base material;
[0122] Carbon fibers, modified reinforcing resin, heat-permeable fiber microsheets and permeable base materials are mixed to obtain an environmentally friendly high-tenacity fiber-reinforced composite material.
[0123] Comparative Example 4
[0124] The environmentally friendly high-tenacity fiber-reinforced composite material, calculated by weight, comprises the following raw materials:
[0125] 52 parts of modified reinforcing resin, 21 parts of heat-transmitting fiber microsheets, 52 parts of cement base material, 17.5 parts of surfactant, 15 parts of surface toughening agent, 23.5 parts of styrene-butadiene-styrene block copolymer;
[0126] The raw materials for preparing the heat-transmitting fiber micro-sheets include, by weight: 6 parts of copper powder, 25 parts of kenaf fiber powder, 8 parts of adhesive, and 25 parts of silk sheets;
[0127] The raw materials for preparing the modified reinforced resin include, by weight: 15 parts of liquid nitrile rubber, 15 parts of polyvinyl alcohol tert-butyral, 6 parts of vinyl acetate, 6 parts of Yajing stone, 6 parts of Jingzuancai and 45 parts of epoxy resin;
[0128] A method for preparing the above-mentioned environmentally friendly high-tenacity fiber-reinforced composite material comprises the following steps:
[0129] Modified reinforced resin: (i) Liquid nitrile rubber and polyvinyl alcohol tert-butyral are mixed and stirred for 20 minutes, at a stirring speed of 120 r / min and at a temperature of 30°C to obtain a mixed glue; (ii) Vinyl acetate, Yajing stone and Jingzuancai are mixed and stirred for 25 minutes, at a stirring speed of 120 r / min and at a temperature of 30°C to obtain a mixture; (iii) The mixed glue, the mixture and epoxy resin are mixed and stirred for 60 minutes, at a stirring speed of 80 r / min and at a temperature of 30°C;
[0130] Kenaf fiber: (i) taking kenaf leaves, washing them, and drying them; (ii) rolling them under a stone mill; (iii) spreading the rolled kenaf leaves flat on a screen; (iv) using a high-pressure water gun to wash the juice out of the rolling, leaving the fiber strands for later use; (v) spraying the fiber strands with a vulcanizing agent at 120°C for 6 hours, and then drying the fiber strands with hot air at 70°C until the fiber strands are completely dry; (v) grinding the fiber strands to obtain kenaf fiber powder;
[0131] Heat-transmitting fiber micro-sheets: (i) copper powder with a diameter of 7 μm and kenaf fiber powder with a diameter of 0.8 nm are mixed and stirred for 25 min at a stirring speed of 50 r / min to obtain a mixture; (ii) silk is woven into a 15 cm silk sheet using a textile machine, and an adhesive is sprayed on the silk sheet; (iii) the mixture is evenly spread on the silk sheet using a vibrating spreader, and the mixture is naturally air-dried; (iv) the silk sheet is cut to obtain a 6 nm heat-transmitting fiber micro-sheet;
[0132] The rubber grass rubber and the α-cyanoacrylate glue solution are mixed (the mass ratio of the rubber grass rubber to the α-cyanoacrylate glue solution is 1:1) to obtain a surface toughening agent;
[0133] Mixing a cement base material and a styrene-butadiene-styrene block copolymer to obtain a base material mixture;
[0134] mixing the base material mixture and the surfactant to obtain a permeable base material;
[0135] The modified reinforcing resin, the heat-transmitting fiber microsheets and the permeable base material are mixed to obtain an environmentally friendly high-tenacity fiber-reinforced composite material.
[0136] Comparative Example 5
[0137] The environmentally friendly high-tenacity fiber-reinforced composite material, calculated by weight, comprises the following raw materials:
[0138] 28 parts of carbon fiber, 50 parts of modified reinforcing resin, 50 parts of cement base material, 16.5 parts of surfactant, 14.2 parts of surface toughening agent, 22.3 parts of styrene-butadiene-styrene block copolymer;
[0139] The raw materials for preparing carbon fiber include, by weight: 8 parts of 0.03 μm carbon fiber precursor, 15 parts of 0.3 μm carbon fiber precursor and 15 parts of 3 μm carbon fiber precursor;
[0140] The raw materials for preparing the modified reinforced resin include, by weight: 15 parts of liquid nitrile rubber, 15 parts of polyvinyl alcohol tert-butyral, 6 parts of vinyl acetate, 6 parts of Yajing stone, 6 parts of Jingzuancai and 45 parts of epoxy resin;
[0141] A method for preparing the above-mentioned environmentally friendly high-tenacity fiber-reinforced composite material comprises the following steps:
[0142] Carbon fiber: (i) The surface of carbon fiber precursors with diameters of 0.03 μm, 0.3 μm, and 3 μm was laser treated, and 30 grooves with a radius of 0.003 μm were etched on the surface of the carbon fiber precursors; (ii) The carbon fiber precursors with diameters of 0.03 μm, 0.3 μm, and 3 μm were vibrated and mixed using a vibration plate, and the vibration time was controlled to be 25 min;
[0143] Modified reinforced resin: (i) Liquid nitrile rubber and polyvinyl alcohol tert-butyral are mixed and stirred for 20 minutes, at a stirring speed of 120 r / min and at a temperature of 30°C to obtain a mixed glue; (ii) Vinyl acetate, Yajing stone and Jingzuancai are mixed and stirred for 25 minutes, at a stirring speed of 120 r / min and at a temperature of 30°C to obtain a mixture; (iii) The mixed glue, the mixture and epoxy resin are mixed and stirred for 60 minutes, at a stirring speed of 80 r / min and at a temperature of 30°C;
[0144] The rubber grass rubber and the α-cyanoacrylate glue solution are mixed (the mass ratio of the rubber grass rubber to the α-cyanoacrylate glue solution is 1:1) to obtain a surface toughening agent;
[0145] Mixing a cement base material and a styrene-butadiene-styrene block copolymer to obtain a base material mixture;
[0146] mixing the base material mixture and the surfactant to obtain a permeable base material;
[0147] Carbon fibers, modified reinforcing resins and permeable base materials are mixed to obtain environmentally friendly high-toughness fiber-reinforced composite materials.
[0148] Comparative Example 6
[0149] The environmentally friendly high-tenacity fiber-reinforced composite material, calculated by weight, comprises the following raw materials:
[0150] 25 parts of carbon fiber, 45 parts of modified reinforcing resin, 18 parts of heat-transmitting fiber microsheets, 45 parts of cement base material, 15 parts of surfactant, 13 parts of surface toughening agent (rubber grass rubber accounts for 100%), and 20 parts of styrene-butadiene-styrene block copolymer;
[0151] The raw materials for preparing the heat-transmitting fiber micro-sheets include, by weight: 6 parts of copper powder, 25 parts of kenaf fiber powder, 8 parts of adhesive, and 25 parts of silk sheets;
[0152] The raw materials for preparing carbon fiber include, by weight: 8 parts of 0.03 μm carbon fiber precursor, 15 parts of 0.3 μm carbon fiber precursor and 15 parts of 3 μm carbon fiber precursor;
[0153] The raw materials for preparing the modified reinforced resin include, by weight: 15 parts of liquid nitrile rubber, 15 parts of polyvinyl alcohol tert-butyral, 6 parts of vinyl acetate, 6 parts of Yajing stone, 6 parts of Jingzuancai and 45 parts of epoxy resin;
[0154] A method for preparing the above-mentioned environmentally friendly high-tenacity fiber-reinforced composite material comprises the following steps:
[0155] Carbon fiber: (i) The surface of carbon fiber precursors with diameters of 0.03 μm, 0.3 μm, and 3 μm was laser treated, and 30 grooves with a radius of 0.003 μm were etched on the surface of the carbon fiber precursors; (ii) The carbon fiber precursors with diameters of 0.03 μm, 0.3 μm, and 3 μm were vibrated and mixed using a vibration plate, and the vibration time was controlled to be 25 min;
[0156] Modified reinforced resin: (i) Liquid nitrile rubber and polyvinyl alcohol tert-butyral are mixed and stirred for 20 minutes, at a stirring speed of 120 r / min and at a temperature of 30°C to obtain a mixed glue; (ii) Vinyl acetate, Yajing stone and Jingzuancai are mixed and stirred for 25 minutes, at a stirring speed of 120 r / min and at a temperature of 30°C to obtain a mixture; (iii) The mixed glue, the mixture and epoxy resin are mixed and stirred for 60 minutes, at a stirring speed of 80 r / min and at a temperature of 30°C;
[0157] Kenaf fiber: (i) taking kenaf leaves, washing them, and drying them; (ii) rolling them under a stone mill; (iii) spreading the rolled kenaf leaves flat on a screen; (iv) using a high-pressure water gun to wash the juice out of the rolling, leaving the fiber strands for later use; (v) spraying the fiber strands with a vulcanizing agent at 120°C for 6 hours, and then drying the fiber strands with hot air at 70°C until the fiber strands are completely dry; (v) grinding the fiber strands to obtain kenaf fiber powder;
[0158] Heat-transmitting fiber micro-sheets: (i) copper powder with a diameter of 7 μm and kenaf fiber powder with a diameter of 0.8 nm are mixed and stirred for 25 min at a stirring speed of 50 r / min to obtain a mixture; (ii) silk is woven into a 15 cm silk sheet using a textile machine, and an adhesive is sprayed on the silk sheet; (iii) the mixture is evenly spread on the silk sheet using a vibrating spreader, and the mixture is naturally air-dried; (iv) the silk sheet is cut to obtain a 6 nm heat-transmitting fiber micro-sheet;
[0159] Mixing a cement base material and a styrene-butadiene-styrene block copolymer to obtain a base material mixture;
[0160] mixing the base material mixture and the surfactant to obtain a permeable base material;
[0161] Carbon fibers, modified reinforcing resin, heat-permeable fiber microsheets, surface toughening agents and permeable base materials are mixed to obtain an environmentally friendly high-toughness fiber-reinforced composite material.
[0162] Comparative Example 7
[0163] The environmentally friendly high-tenacity fiber-reinforced composite material, calculated by weight, comprises the following raw materials:
[0164] 25 parts of carbon fiber, 45 parts of modified reinforcing resin, 18 parts of heat-transmitting fiber microsheets, 45 parts of cement base material, 15 parts of surfactant, 13 parts of surface toughening agent (α-cyanoacrylate glue solution accounts for 100%), and 20 parts of styrene-butadiene-styrene block copolymer;
[0165] The raw materials for preparing the heat-transmitting fiber micro-sheets include, by weight: 6 parts of copper powder, 25 parts of kenaf fiber powder, 8 parts of adhesive, and 25 parts of silk sheets;
[0166] The raw materials for preparing carbon fiber include, by weight: 8 parts of 0.03 μm carbon fiber precursor, 15 parts of 0.3 μm carbon fiber precursor and 15 parts of 3 μm carbon fiber precursor;
[0167] The raw materials for preparing the modified reinforced resin include, by weight: 15 parts of liquid nitrile rubber, 15 parts of polyvinyl alcohol tert-butyral, 6 parts of vinyl acetate, 6 parts of Yajing stone, 6 parts of Jingzuancai and 45 parts of epoxy resin;
[0168] A method for preparing the above-mentioned environmentally friendly high-tenacity fiber-reinforced composite material comprises the following steps:
[0169] Carbon fiber: (i) The surface of carbon fiber precursors with diameters of 0.03 μm, 0.3 μm, and 3 μm was laser treated, and 30 grooves with a radius of 0.003 μm were etched on the surface of the carbon fiber precursors; (ii) The carbon fiber precursors with diameters of 0.03 μm, 0.3 μm, and 3 μm were vibrated and mixed using a vibration plate, and the vibration time was controlled to be 25 min;
[0170] Modified reinforced resin: (i) Liquid nitrile rubber and polyvinyl alcohol tert-butyral are mixed and stirred for 20 minutes, at a stirring speed of 120 r / min and at a temperature of 30°C to obtain a mixed glue; (ii) Vinyl acetate, Yajing stone and Jingzuancai are mixed and stirred for 25 minutes, at a stirring speed of 120 r / min and at a temperature of 30°C to obtain a mixture; (iii) The mixed glue, the mixture and epoxy resin are mixed and stirred for 60 minutes, at a stirring speed of 80 r / min and at a temperature of 30°C;
[0171] Kenaf fiber: (i) taking kenaf leaves, washing them, and drying them; (ii) rolling them under a stone mill; (iii) spreading the rolled kenaf leaves flat on a screen; (iv) using a high-pressure water gun to wash the juice out of the rolling, leaving the fiber strands for later use; (v) spraying the fiber strands with a vulcanizing agent at 120°C for 6 hours, and then drying the fiber strands with hot air at 70°C until the fiber strands are completely dry; (v) grinding the fiber strands to obtain kenaf fiber powder;
[0172] Heat-transmitting fiber micro-sheets: (i) copper powder with a diameter of 7 μm and kenaf fiber powder with a diameter of 0.8 nm are mixed and stirred for 25 min at a stirring speed of 50 r / min to obtain a mixture; (ii) silk is woven into a 15 cm silk sheet using a textile machine, and an adhesive is sprayed on the silk sheet; (iii) the mixture is evenly spread on the silk sheet using a vibrating spreader, and the mixture is naturally air-dried; (iv) the silk sheet is cut to obtain a 6 nm heat-transmitting fiber micro-sheet;
[0173] Mixing a cement base material and a styrene-butadiene-styrene block copolymer to obtain a base material mixture;
[0174] mixing the base material mixture and the surfactant to obtain a permeable base material;
[0175] Carbon fibers, modified reinforcing resin, heat-permeable fiber microsheets, surface toughening agents and permeable base materials are mixed to obtain an environmentally friendly high-toughness fiber-reinforced composite material.
[0176] 3. Experimental Methods
[0177] 3.1 Hardness test
[0178] 1) Experimental Materials
[0179] Brick masonry (1*0.5*1 cubic meter) (70 pieces)
[0180] 2) Experimental procedures
[0181] ① Take 10 portions of the composite materials prepared in Examples 1-3 and Comparative Examples 1-4, each with a volume of 30*30*30 cubic centimeters;
[0182] ② The same composite material is applied between the bricks in the same brick masonry, and the same composite material is applied to the four faces of the brick masonry perpendicular to the ground and allowed to dry naturally;
[0183] ③Fix the 70 brick masonry on the ground;
[0184] ④ Use a pneumatic dynamometer to generate a force of 120 kN at the same position of each brick stack;
[0185] ⑤ Take the average value of the integrity data of 10 brick masonry bodies using the composite material prepared in the same embodiment or comparative example, as shown in Table 1;
[0186] Table 1:
[0187] project Completeness Example 1 80% Example 2 85% Example 3 93% Comparative Example 1 74% Comparative Example 2 76% Comparative Example 3 71% Comparative Example 4 54%
[0188] It can be seen from the above table that compared with Examples 1-2 and Comparative Examples 1-4, the composite material prepared by Example 3, when used for brick masonry, effectively improves the stress-bearing capacity of the brick masonry by using carbon fiber filaments of different sizes. When subsequently applied to building walls, the stress-bearing capacity and anti-destruction ability of the wall can be effectively enhanced.
[0189] 3.2. Permeability test
[0190] 1) Experimental Materials
[0191] Brick masonry (1*0.5*1 cubic meter) (20 pieces)
[0192] 2) Experimental procedures
[0193] ① Take 10 portions of the composite materials prepared in Example 3 and Comparative Example 5, each with a volume of 30*30*30 cubic centimeters;
[0194] ② The same composite material is applied between the bricks in the same brick masonry, and the same composite material is applied to the four faces of the brick masonry perpendicular to the ground, and allowed to dry naturally for 4 days;
[0195] ③ Use a cutting machine to cut 20 brick masonry bodies (width and length remain unchanged) to obtain the cross section of the brick masonry bodies;
[0196] ④ Calculate the cross-sectional area of the composite material after solidification on the cross-section of the brick masonry;
[0197] ⑤ Take the average value of the ratio of the cross-sectional area of 10 composite materials prepared in the same embodiment or comparative example to the surface (length*width) of the brick masonry after solidification, as shown in Table 2;
[0198] Table 2:
[0199] project Cross-sectional area Example 3 65% Comparative Example 5 32%
[0200] It can be seen from the above table that compared with comparative example 5, when Example 3 is used on brick masonry, the composite material prepared by Example 3 has better penetration ability, so that more composite material can penetrate into the interior of the brick through the pores on the brick, so that the composite material has better adhesion ability, thereby improving the traction between bricks and bricks, and at the same time, it also helps to avoid separation of the composite material and bricks.
[0201] 3.3. Permeability test
[0202] 1) Experimental Materials
[0203] Brick masonry (1*0.5*1 cubic meter) (30 pieces)
[0204] 2) Experimental procedures
[0205] ① Take 10 portions of the composite materials prepared in Example 3 and Comparative Examples 6-7, each with a volume of 30*30*30 cubic centimeters;
[0206] ② The same composite material is applied between the bricks in the same brick masonry, and the same composite material is applied on the same surface of the brick masonry perpendicular to the ground;
[0207] ③ The surface of the composite material is rubbed lightly with fingers to check the hardness, and a person is manually judged whether the surface of the composite material is solidified, and the solidification time of the composite material is recorded;
[0208] ④ Take the average value of the solidification time data of 10 composite materials prepared in the same embodiment or comparative example, as shown in Table 3;
[0209] Table 3:
[0210] project Surface solidification time Example 3 2h10min Comparative Example 6 3h20min Comparative Example 7 4h10min
[0211] It can be seen from the above table that compared with comparative examples 6-7, when the composite material prepared by Example 3 is used for brick masonry, the surface solidification speed of the composite material is the fastest, which helps to shorten the construction period and at the same time reduces the probability of debris and dust at the construction site adhering to the surface of the composite material.
[0212] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. Environmentally friendly high-tenacity fiber-reinforced composite material, characterized in that: The raw materials for its preparation include, by weight: 20-25 parts of carbon fiber, 30-45 parts of modified reinforcing resin, 10-18 parts of heat-transmitting fiber microsheets, 35-45 parts of cement base material, 10-15 parts of surfactant, 10-13 parts of surface toughening agent, 10-20 parts of styrene-butadiene-styrene block copolymer; Wherein, the raw materials for preparing the heat-transmitting fiber micro-sheets include, by weight: 3-6 parts of copper powder, 15-25 parts of kenaf fiber powder, 5-8 parts of adhesive, and 15-25 parts of silk sheets.
2. The environmentally friendly high-tenacity fiber-reinforced composite material according to claim 1, characterized in that: The preparation process of the carbon fiber is as follows: (i) subjecting the surfaces of carbon fiber precursors with diameters of 0.01-0.03 μm, 0.1-0.3 μm, and 1-3 μm to laser treatment, and etching 10-30 grooves with a radius of 0.001-0.003 μm on the surfaces of the carbon fiber precursors; (ii) vibrating and mixing the carbon fiber precursors with diameters of 0.01-0.03 μm, 0.1-0.3 μm, and 1-3 μm using a vibration disk, and controlling the vibration time to be 15 min-25 min.
3. The environmentally friendly high-tenacity fiber-reinforced composite material according to claim 2, characterized in that: The raw materials for preparing the carbon fiber include, by weight: 5-8 parts of 0.01-0.03 μm carbon fiber precursor, 10-15 parts of 0.1-0.3 μm carbon fiber precursor and 10-15 parts of 1-3 μm carbon fiber precursor.
4. The environmentally friendly high-tenacity fiber-reinforced composite material according to claim 1, characterized in that: The preparation process of the modified reinforced resin is: (i) Mixing and stirring liquid nitrile rubber and polyvinyl alcohol tert-butyral for 10-20 min, at a stirring speed of 100-120 r / min and at a temperature of 25-30°C to obtain a mixed rubber; (ii) Mixing and stirring vinyl acetate, Yajing stone and Jingzuancai for 15-25 min, at a stirring speed of 100-120 r / min and at a temperature of 25-30°C to obtain a mixture; (iii) Mixing and stirring the mixed rubber, the mixture and epoxy resin for 40-60 min, at a stirring speed of 60-80 r / min and at a temperature of 25-30°C.
5. The environmentally friendly high-tenacity fiber-reinforced composite material according to claim 4, characterized in that: The raw materials for preparing the modified reinforced resin include, by weight: 10-15 parts of liquid nitrile rubber, 10-15 parts of polyvinyl alcohol tert-butyral, 3-6 parts of vinyl acetate, 3-6 parts of Yajing stone, 3-6 parts of Jingzuancai and 30-45 parts of epoxy resin.
6. The environmentally friendly high-tenacity fiber-reinforced composite material according to claim 1, characterized in that: The preparation process of the heat-transmitting fiber microsheet is as follows: (i) mixing copper powder with a diameter of 4-7 μm and kenaf fiber powder with a diameter of 0.5-0.8 nm for 15-25 min and a stirring speed of 30-50 r / min to obtain a mixture; (ii) using a textile machine to weave silk into 10-15 cm silk sheets, and spraying an adhesive on the silk sheets; (iii) using a vibrating spreader to evenly scatter the mixture on the silk sheets, and air-drying the silk sheets naturally; (iv) cutting the silk sheets to obtain 3-6 nm heat-transmitting fiber microsheets.
7. The environmentally friendly high-tenacity fiber-reinforced composite material according to claim 1, characterized in that: The preparation process of the kenaf fiber is as follows: (i) Take kenaf leaves, wash them and dry them; (ii) Roll them under a stone mill; (iii) Spread the rolled kenaf leaves flat on a screen; (iv) Use a high-pressure water gun to wash the juice out of the rolling, and keep the fiber strands for later use; (v) Use a vulcanizing agent at 110-120°C to spray the fiber strands for 4-6 hours, and then use 60-70°C hot air to blow the fiber strands until the fiber strands are completely dry; (v) Grind the fiber strands to obtain kenaf fiber powder.
8. A method for preparing an environmentally friendly high-tenacity fiber-reinforced composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, mixing rubber grass rubber and α-cyanoacrylate glue solution (the mass ratio of rubber grass rubber to α-cyanoacrylate glue solution is 1:1) to obtain a surface toughening agent; S2, mixing a cement base material and a styrene-butadiene-styrene block copolymer to obtain a base material mixture; S3, mixing the base material mixture and the surfactant to obtain a permeable base material; S4, mixing carbon fibers, modified reinforcing resin, heat-permeable fiber microsheets, surface toughening agents and permeable base materials to obtain an environmentally friendly high-toughness fiber-reinforced composite material.